PENERAPAN METODE ALM (Audio Lingual Method) DALAM PEMBELAJARAN SPEAKING ENGLISH DI SMP ISLAM AN-NIDHOMIYAH PAMEKASAN - MS, S. Sumihatul Ummah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
The purpose of this reasearch is to describe steps in the implementing of ALM in learning Speaking English, to know parts of Speaking English activities that can make the students more interest and active in their learning, the teacherâs obstacles in teaching Speaking English, and the teacherâs ways to solve the problemsÂ  by using ALM. It is a qualitative descriptive research. While the techniques of collecting data used observation, interview, and documentation. The reaseach result is concluded that there are three steps in teaching and learning Speaking English. They are (pre-teaching), (whilst-teaching), and (post-teaching).Â  The teacher used six techniques of ALM in teaching Speaking English namely dialog memorization, backward build up (expansion) drill, and repetition drillÂ  at the first observation. For second observation, teacher used the technique of chain drill, question and answer drill, dan complete the dialog. Besides, teacherâs obstacles in teaching Speaking English are time allotment, teacherâs feeling (boring and tiring), and teaching media minimally. But, the teacher could solve the problems by giving homework somtimes, having enjoy in present the material, and collaborating the instructional material with simple media at the school.